Immune Modulatory Short Noncoding RNAs Targeting the Glioblastoma Microenvironment - Wei, Jun; Gilboa, Eli; Calin, George A.; Heimberger, Amy B. (Frontiers in Oncology, 2021)
Glioblastomas are complex and heterogeneous brain tumors with a poor prognosis. Glioblastoma cells can communicate with their surroundings to create a tumor-permissive and immunosuppressive microenvironment. Short non-coding RNAs are relevant mediators of the dynamic crosstalk among cancer, immune, and stromal cells in establishing the glioblastoma microenvironment. In addition to the ease of combinatorial strategies that are capable of multi-modal modulation for both reversing immune suppression and enhancing anti-tumor immunity, their small size provides an opportunity to overcome the limitations of the blood-brain-barrier (BBB). To enhance glioblastoma delivery, oligonucleotides have been encapsulated within or conjugated with delivery vehicles for enhanced membrane penetration, improved payload, and tissue-specific delivery. Here we focus on the role of RNA therapeutics targeting the glioblastoma microenvironment by appraising which types of nucleotides are most effective in immune modulation especially in the glioblastoma microenvironment, lead therapeutic candidates, and how to optimize delivery of the therapeutic RNAs and their conjugates specifically to the glioblastoma microenvironment.